How does ownership of farm implements affect investment in other farm implements when farmers' liquidity constraint is relaxed? Insights from Nigeria - Takeshima, Hiroyuki; Salau, Sheu (International Food Policy Research Institute, 2011)
Mechanization is a key to agricultural productivity growth in developing countries. Farm implements, ranging from hand tools to draft animals to milling machines to power tillers and tractors, often play complementary roles with each other, and supporting adoption of certain farm implements may also speed up adoption of others. In the absence of credit, insurance, or information, however, such complementarity may be reduced. This study analyzes how the ownership of particular farm implements by Nigerian farmers affected their investment in other farm implements under a project that provided matching grants for the acquisition of various types of farm implements. We found that ownership of certain farm implements increased farmers' investment in the same implements but reduced their investment in other, potentially complementary, implements. We argue that these effects may be partly explained by high operating and maintenance costs associated with the use of farm equipment in these countries. Ownership of farm equipment may provide a good indicator of farmers' potential willingness to invest in the same of different farm equipment. At the same time, a public project supporting farmers' investment in farm equipment should provide financial support not only for the acquisition of farm implements but also for their operation and maintenance.